Pengembangan Media Pembelajaran Tari Topeng Berbasis Android dengan Metode Analysis Design Development Implementation and Evaluation - Ade Irma Purnamasari; Andi Setiawan; Kaslani Kaslani (P3M Politeknik Negeri Cilacap, 2021)
Mask Dance is one of Cirebon's traditional arts in Indonesia and has a variety of types and meanings in accordance with the symbols depicting characters such as in popular stories. The young generation in their activities cannot be separated from using internet technology, one of which is social media, so that it affects their less concern for art and traditions that have been inherent in society. From these problems, it is necessary to make Mask Dance learning media by utilizing android technology. This study uses the ADDIE method through the stages of Analysis, Design, Development, Implementation, and Evaluation as a guide in building learning tools. The results of this study are an Android-based application of Mask Dance learning media to introduce Mask Dance starting from history, descriptions, types of dance, how to dance to Mask Dance, and quizzes to evaluate understanding of learning. With this learning media, it can make it easier for students to learn mask dance among students and other young generations. From the test results using a black box, it shows that the functions in the application have been running according to their function, while the test results to the respondents obtained a value of 84.27% with good criteria for the application so that this application can be used as a medium for learning Mask Dance.